Determinants of trust: The role of personal experiences - Schwerter, Frederik; Zimmermann, Florian (Games and economic behavior, 2020)
Social interactions pervade daily life and thereby create an abundance of social experiences. Such personal experiences likely shape what we believe and who we are. In this paper, we ask if and how personal experiences from social interactions determine individuals' inclination to trust others? In a laboratory experiment, we manipulate social experiences prior to measuring participants' willingness to trust others. We contrast this situation with a non-social control condition where we keep all aspects of the prior experiences identical, except that we remove the social dimension. Subjects' willingness to trust is substantially higher after a positive social experience relative to a negative social experience. No such effect is obtained in the non-social control condition. Our results cannot be explained by rational learning as well as income and reference point effects. Delving into the underlying mechanisms, we provide evidence that non-standard belief patterns are an important driver of experience effects.